Transmission processes of religious knowledge and ritual practice in Alevism between innovation and reconstruction - Zimmermann, Johannes; Karolewski, Janina; Langer, Robert (History of Culture of the Modern Near and Middle East, 2019)
Knowledge transmission in Alevism – Ritual practice – Written tradition – Oral lore – Scripturalisation – Memory and commemoration – Manuscripts – New media – Mimetics and imitation – Poet-minstrels – Gender roles – Transnational space – Yezidism.